Comparative reproductive biology, and aspects of behaviour and ecology of Agama aculeata aculeata and Agama planiceps planiceps (Reptilia: Agamidae) in the Windhoek area - Heideman, N. J. L.(Neil Johannes Louizs) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1992.